Peptidomimetic inhibitors of N-myristoyltransferase from human malaria and leishmaniasis parasites - Olaleye,TO; Brannigan,JA; Roberts,SM; Leatherbarrow,RJ; Wilkinson,AJ; Tate,EW (Organic & Biomolecular Chemistry, 2014)
N-Myristoyltransferase (NMT) has been shown to be essential in Leishmania and subsequently validated as a drug target in Plasmodium. Herein, we discuss the use of antifungal NMT inhibitors as a basis for inhibitor development resulting in the first sub-micromolar peptidomimetic inhibitors of Plasmodium and Leishmania NMTs. High-resolution structures of these inhibitors with Plasmodium and Leishmania NMTs permit a comparative analysis of binding modes, and provide the first crystal structure evidence for a ternary NMT-Coenzyme A/myristoylated peptide product complex.